EFEKTIVITAS INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) RUMAH SAKIT UMUM ROEMANI MUHAMMADIYAH SEMARANG - Mitha Karunia Baeti; Mursid Raharjo; Nikie Astorina Yunita Dewanti; Sulistiyani Sulistiyani (Jurnal Kesehatan Masyarakat (Undip), 2022)
The waste management at the Roemani Muhammadiyah General Hospital Semarang uses anaerobic technology with the DEWATS (Decentralized Wastewater Treatment System) system whose outlet test results for COD, BOD and Coliform bacteria are still above the specified quality standards. This study aimed to evaluate aspects of fluid waste management and management, whether it follows existing liquid waste management regulations, and determine the effectiveness of wastewater treatment at Roemani Muhammadiyah General Hospital Semarang. This type of research was a mixed-method with a concurrent triangulation strategy; the research was supported by quantitative data carried out descriptively. The results of the management aspect of the Roemani Muhammadiyah Hospital Semarang is following the regulation of the Minister of Health No. 7 of 2019 concerning Hospital Environmental Health. While liquid waste management is still not following existing laws. Roemani Muhammadiyah Hospital Semarang has been efficient in reducing TSS, BOD, COD and NH3 while for the parameters of Colifom bacteria, WWTP Roemani Muhammadiyah Hospital Semarang is still not efficient in reducing the parameters of Colifom bacteria. Therefore, it is hoped that the hospital will pay more attention to waste water quality, especially that produced by each health service agency.